Ion microprobe discovery of archaean and early proterozoic zircon xenocrysts in southwest Sweden - Cornell, David; Årebäck, Hans; Scherstén, Anders ; 0000-0002-2105-6172 (GFF, 2000)
A single zircon grain dated by ion probe with a minimum age of 3432±30 Ma was found in a microgranite dyke, which cuts norite of 916±11 Ma Hakefjorden Complex at Älgön on the Swedish west coast north of Gothenburg. Zircons are a rare accessory mineral in this dyke. They could be classified by morphology as orthocrysts and xenocrysts. Data from four orthocrysts show that the dyke originated between 911±14 and 916±11 Ma, and was probably derived from the Hakefjorden Complex contact migmatite. Eight of the dated grains are xenocrysts, probably derived from the Stora Le-Marstrand Formation. They have 207Pb-206Pb minimum ages from c.1451 to 3432±6 Ma, and the oldest grain has a probable age of 3457±10 Ma, derived from a discordia regression, with 445±38 Ma lower intercept reflecting Phanerozoic lead loss. This grain is the oldest yet dated in Scandinavia. Together with six >1750 Ma zircon grains in both this sample and a related Stora Le-Marstrand-derived sample, it casts doubt on the prevailing model of incremental crustal growth in Scandinavia, southwestwards from an Archaean core in the northeast of the Baltic Shield. These old ages, together with published Sm-Nd data, also contradict the proposed origin of the Stora Le-Marstrand Formation in an isolated oceanic island arc setting. It is more likely that it formed on the eastern (in present-day terms) margin of an Archaean continent, which did not join Baltica till the Sveconorwegian orogenic cycle.
Keywords: Archaean; Baltic shield; Crustal growth; Dating; Episyenite; Nordsim; Zircon